Life cycle process model of a market-oriented and student centered higher education - Kaklauskas, Artūras; Daniūnas, Alfonsas; Amaratunga, Dilanthi; Urbonas, Vilius; Gudauskas, Renaldas; Lill, Irene; D‘amato, Maurizio; Trinkūnas, Vaidotas; Jackutė, Ieva (International Journal of Strategic Property Management, 2012)
There is not a single definition/explanation about market-orientation education. Two opposite definitions/explanations of pure market-oriented education (Cato, 2010) and social-market-oriented education (Amaratunga, 2009) are provided in the paper. Integrated multiple criteria analysis at the micro-, meso- and macro-levels are needed to increase efficiency of the market-oriented higher education reforms. Market-oriented higher education reforms management involves numerous aspects that should be considered in addition to making educational, pedagogical, didactical, economic, political and legal/regulatory decisions. These must include social, culture, ethical, psychological, environmental, technological, technical, organizational and managerial aspects. This article presents a Life Cycle Process Model of a Market-Oriented and Student Centered Higher Education (developed during BELL-CURVE (Built Environment Lifelong Learning Challenging University Responses to Vocational Education) project’s activities) for such considerations and discusses certain composite parts of it. To demonstrate the application of this research, two Case Studies from Lithuania are submitted for consideration. First Publish Online: 19 Dec 2012